Educational psychology : a development approach - Sprinthall, Richard C.; Sprinthall, Norman A. ([S.l.] : McGraw-Hill Inc.,US, 1990)
The fifth edition of this successful text continues to provide a comprehensive coverage of educational psychology within a developmental framework. This integrating perspective holds that decision making should be closely tied to knowledge of student characteristics and developmental levels.
Keywords: psychology